Analysis of the effect of additional employee income on job satisfaction and employee performance at the population and civil registration office of Serdang Bedagai Regency - Susy Novianty; R Sabrina (Economic: Journal Economic and Business, 2026)
This study aims to analyze the effect of Employee Income Supplement (TPP) on job satisfaction and employee performance, and to examine the role of job satisfaction as an intervening variable at the Population and Civil Registration Office of Serdang Bedagai Regency. This study uses a quantitative approach with an explanatory research design. The research sample consisted of 25 employees who received TPP and was determined using a saturated sampling technique. Data were collected through a questionnaire composed of 51 statements and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that TPP had a positive and significant effect on job satisfaction, job satisfaction had a positive and significant effect on employee performance, while TPP had no significant direct effect on employee performance. In addition, job satisfaction was proven to play a full mediating role in the relationship between TPP and employee performance. These findings indicate that improving employee performance is more effectively achieved through TPP policies that can first increase job satisfaction.